Pengaruh Media Video Animasi Demo Heimlich Maneuver (Choking) terhadap Kemampuan Ibu Menolong Anak Toddler Tersedak - MOCH. MAFTUCHUL HUDA (PT Nuansa Fajar Cemerlang, 2024)
Choking is an emergency condition that often occurs in toddlers and requires quick treatment to avoid death. Most mothers do not apply choking management properly due to lack of information, resulting in less maternal ability. The Heimlich Maneuver demo animation video is the right medium for health education. The purpose of this study is to determine the effectiveness of the Heimlich Maneuver (Choking) demo animation video on the ability of mothers to help toddlers choke. The design of this study quasy experiment. A population of 60 mothers with toddler children, the sample numbered 40 with purposive sampling technique divided into 20 treatment groups and 20 control groups. Maternal ability instruments in the form of questionnaire sheets and observations have been shown validity and reliability. The research intervention was carried out 2 times a day and carried out for 2 consecutive days with a duration of 2 minutes 17 seconds each action. The results of data analysis using the Wilcoxon test in the treatment group p value= 0.000 < α = 0.05 mean that there is an effect of the Heimlich Maneuver (Choking) demo animation video on the mother's ability to help toddlers choke. The results of the Mann Whitney test, post test of the treatment group and the control group, p value = 0.000 <α = 0.05 means that there is a difference between the treatment group and the control group. Animated videos in the form of visual stimulation are a combination of audio stimulation that is interesting, easy to understand, easy to remember, imitated as an action guide and clear video text narration, facilitating the association of knowledge, attitudes, actions to overcome choking toddlers. Video recordings were repeated according to the dose of research intervention, the mother was able to help the toddler choke properly. The results of this demo animation video research can be recommended as an alternative to improve the ability to help toddlers choke.